Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How would I find the following limit? I am thinking I might need to do a Taylor expansion of the exponentials but it hasn't worked out nicely. Thanks for the help.

$$\lim_{p\to 0} \left( \frac{pe^{2tp}}{1-e^{2tp}(1-p)} \right)^k$$

The answer is $(1+2t)^{-k}$.

share|cite|improve this question
Naive application of L'Hopital's: $$\begin{eqnarray} \lim\limits_{p\to 0}\left(\frac{pe^{2tp}}{1-e^{2tp}(1-p)}\right)^k &=&\left(\lim\limits_{p\to 0}\frac{pe^{2tp}}{1-e^{2tp}(1-p)}\right)^k\\ &=&\left(\lim\limits_{p\to 0}\frac{e^{2tp}+2p^2e^{2tp}}{2pe^{2tp}(1-p)-e^{2tp}}\right)^k\\ &=&\left(\lim\limits_{p\to 0}\frac{e^{2tp}+2p^2e^{2tp}}{2pe^{2tp}-(e^{2tp}+2p^2e^{2tp})}\right)^k\\ \end{eqnarray}$$ Perhaps examine similarity to $\frac{x}{x-y}$? – Alex Becker Mar 7 '12 at 0:57
up vote 3 down vote accepted

Have you tried l'Hospital's rule? $$ \lim_{p \to 0} \frac{pe^{2tp}}{1-e^{2tp}(1-p)} = \lim_{p \to 0} \frac{e^{2tp}+p(2t)e^{2tp}}{e^{2tp} - (1-p)(2t)e^{2tp}} = \lim_{p \to 0} \frac{1+2tp}{1-(1-p)(2t)} = \frac {1}{1-2t} $$ Just use the product rule and the case $k=1$ then.

Hope that helps,

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.